Design and Development of Mini Portable Cooler for Breastmilk Storage - Abd Malek, Norhazwani; Osman, Siti Zulaika; Ehsan, Nurhusna Mohamad; Roslan, Nurzanariah; Rosli, Mohd Fakhri (International Journal of Engineering and Technology, 2018)
This paper presents the design and development of a mini portable cooler that utilizes the Peltier effect to cool the human expressed breast milk (EBM) within 24 hours at the temperature range between 4°C-15°C to maintain the high quality of the EBM for use at a later date and the health of the baby who consume it. It is developed to overcome the tediousness of using cooler bag/box, which requires ice packs that need repetitive freezing. A few prototypes with different sizes and body materials, namely polystyrene, polypropylene and aluminium, were successfully developed and tested to get the minimum temperature using 5V power supply. In all graphs, the temperature is decreasing with time. The smallest size of the cooled space (18cm of width, 12cm of length and 14cm of height) has the lowest temperature compared to the other sizes for each body material. However, the lowest temperature of all body materials is obtained from aluminium with 11.2°C at 100 minutes. It also reaches below 15°C the fastest which is at 80 minutes compared to the other prototypes that need longer time. All in all, aluminium is the best body material for the mini portable cooler developed in this project.